2019
DOI: 10.2147/ott.s215701
|View full text |Cite
|
Sign up to set email alerts
|

<p>Transcription factor E2F1 positively regulates interferon regulatory factor 5 expression in non-small cell lung cancer</p>

Abstract: Lung cancer is the most common malignant tumor in the world, and its incidence and mortality are very high. This study focuses on the mechanism of non-small cell lung cancer to find new therapeutic targets. Methods: We used RT-PCR and Western blot to verify the linear relationship between E2F1 and IRF5 in normal lung tissue and lung cancer tissues. Secondly, we used overexpression and knock down E2F1 in cell lines to detect the expression of IRF5. The prime enzyme reporter plasmid verified that E2F1 binds to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In relation to this, accumulating evidence also revealed the involvement of E2F1 in the progression of NSCLC. 8,23 We then validated the upregulation of E2F1 expression in A549 cells, a NSCLC cell line, and uncovered that E2F1 could augment the viability, migration, and invasion of NSCLC cells. Our findings corroborate several previous studies where E2F1 was found to promote the proliferation and migration of NSCLC cells through activating transforming growth factor (TGF)-beta and also other pathways.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In relation to this, accumulating evidence also revealed the involvement of E2F1 in the progression of NSCLC. 8,23 We then validated the upregulation of E2F1 expression in A549 cells, a NSCLC cell line, and uncovered that E2F1 could augment the viability, migration, and invasion of NSCLC cells. Our findings corroborate several previous studies where E2F1 was found to promote the proliferation and migration of NSCLC cells through activating transforming growth factor (TGF)-beta and also other pathways.…”
Section: Discussionmentioning
confidence: 98%
“… 5 Notably, recent studies have pointed out the involvement of E2F1 activation in hepatocarcinogenesis, the progression of hepatocellular carcinoma, and also the brain metastasis of lung adenocarcinoma. 6 , 7 Although there also exist reports on the correlation between E2F1 and NSCLC, such as E2F1 activating IRF5 transcription in NSCLC 8 and LINC00461 promoting NSCLC cell proliferation through modulating E2F1, 9 the specific regulation mechanism of E2F1 on NSCLC progression remains unclear. In this sense, the present study was aimed to explore the role of E2F1 in the pathogenesis of NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…The following primers sequences (Stoleriu et al [ 27 ]) were utilized in the research: sense: 5′-GACGUGUCAGGACCUUCGU-3′, and antisense: 5′-ACGAAGGUCCUGACACGUC-3′. The overexpression plasmid pcDNA-E2F1 and its corresponding negative control plasmid pcDNA3.1 were kept by our laboratory [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…The mutated sequence of the E2F1-A binding site (−64 ATA GGC GCC GCC-53) was 5′-ATA TTA TAA GCC-3′, and the mutated sequence of the E2F1-B binding site (+41 CGG GCG GGA GG +51) was 5′-CGG ATA GGT GG-3′. The overexpression plasmid pENTER-E2F1 (pE2F1) and the corresponding control plasmid pENTER (TsingKe Biological Technology) were supplied by our lab ( 20 ). The double-stranded siRNAs ( Table I ) were synthesized and purified by high-performance chromatography by Shanghai GenePharma Co., Ltd.…”
Section: Methodsmentioning
confidence: 99%